Sentury II. - Mead, Syd, ....- (Culver City : Designstudio, 2010)
The long awaited next book from legendary Syd Mead has finally arrived after nine years. Loyal fans and art enthusiasts will rejoice in being able to view what Syd Mead has been imagining for nearly the past decade. Having illustrated the future for us for the past 40 years, Syd Mead continues to amaze and surprise us with his stunning pieces no matter how much of the future we have seen from the start of his career to present day. Looking through his unrivaled artwork, we still find ourselves continuously waiting for his future to be in our present. Images from countless conceptual projects as well as realized ones will be included in this fantastic visual voyage into the future with the one and only Visual Futurist, Syd Mead.